Does Vitamin D Status Correlate with Cardiometabolic Risk Factors in Adults with Growth Hormone Deficiency? - Uzunova, Ivayla; Kirilov, Georgi; Zacharieva, Sabina; Zlatareva, Naydenka; Kalinov, Krasimir (Hormone and Metabolic Research, 2017)
Apart from being individually associated with cardiometabolic health, 25(OH)D and IGF-1 interplay with a positive correlation between them, which raises questions about the role of vitamin D for the adverse cardiovascular (CV) risk profile in hyposomatotropism. Thus, we aimed to investigate vitamin D status in GH deficiency (GHD) and the association between 25(OH)D and metabolic syndrome (MetS), its components, and other surrogate markers of CV risk. A total of 129 GHD adults (childhood-onset GHD, 41.9%) underwent blood testing (glucose, insulin, lipid profile, uric acid); blood pressure, anthropometric and bioelectrical-impedance measurements. Other CV risk markers were examined in a subsample of the initial population – hsCRP, adiponectin, and asymmetric dimethylarginine (n=88); carotid intima-media thickness (n=44). Total serum 25(OH)D, measured by electro-chemiluminescence binding assay, was used for vitamin D status assessment (adequate,≥30 ng/ml; insufficient, 20–29.9 ng/ml; deficient,<20 ng/ml). Data demonstrated high prevalence of hypovitaminosis D in GHD (deficiency 79.1%; insufficiency 14.7%), with lower 25(OH)D among adult-onset GHD subjects (14.0±7.2 vs. 16.8±8.0 ng/ml, p=0.039) and patients with MetS (11.8±4.5 vs. 16.3±8.1 ng/ml, p<0.0001). 25(OH)D correlated negatively and weakly with BMI, waist circumference, percent body fat, visceral fat area, and systolic BP. Regardless of whether vitamin D is a cause or a consequence of these metabolic abnormalities, 25(OH)D testing in hyposomatotropism is advisable. Normalization of vitamin D status is not proven to improve CV outcomes in general population, but it might have favorable effects in GHD, as its benefits might be restricted to patients with both low 25(OH)D and certain risk factors.
Keywords: hyposomatotropism; hypovitaminosis D; cardiovascular risk; obesity; systolic blood pressure